The Lion's Den - St. John, Katherine, 1979- (Grand Central Publishing, 2020)
"Belle likes to think herself immune to the dizzying effects of fabulous wealth. But when her best friend, Summer, invites her on a glamorous girls' getaway to the Mediterranean aboard her billionaire boyfriend's yacht, the only sensible answer is yes. Belle hopes the trip will be a much-needed break from her stalled acting career and uniquely humiliating waitressing job, but once aboard the luxurious Lion's Den, it becomes clear that all is not as it seems. The dream vacation quickly devolves into a nightmare as Belle and the handful of other girlfriends Summer has invited are treated more like prisoners than guests by their controlling host, and Belle comes to see Summer for what she truly is: a vicious gold digger who will stop at nothing to get what she wants. Belle soon realizes she's going to have to keep her wits about her--and her own big secret close to her chest--if she wants to make it off the yacht alive"--